Süleyman Fâzil Efendi̇’ni̇n el-Fevâʾi̇du’s-seni̇yye fî şerhi̇’l-ʿAkāʾi̇di̇’l-ʿAdudi̇yye’si̇ : Tahki̇k ve tahli̇l - Sultan, Zekeriya (My University, 2023)
VIII. (XIV.) yüzyılın önemli kelâm, usûl ve dil âlimlerinden olan Adudüddîn el-Îcî’nin (ö. 756/ 1355) Eş‘arî kelamı üzerinden Ehl-i Sünnet akaidini takrir ettiği el-ʿAkāʾidü’l-ʿAdudiyye isimli eseri çok sayıda âlim tarafından şerh ve hâşiye yazımına konu olmuştur. Bu şerhlerden biri Ayasofya kürsü şeyhi, vâiz ve muhaddis olan Süleyman Fâzıl Efendi’nin (ö. 1134/ 1722) el-Fevâʾidu’s-seniyye fî şerhi’l-ʿAkāʾidi’l-ʿAdudiyye’sidir. Bu çalışmada Süleyman Fâzıl Efendi’nin hayatı ve eserleri ele alınarak söz konusu şerhinin tahkik ve tahlili yapılmıştır. Bu çerçevede şerhin nüshaları tanıtılmış, özellikleri ayırt edilmiş ve eserin ismi, müellife aidiyeti, müellifin şerhte uyguladığı yöntem ve başvurduğu kaynaklar hakkında bilgi verilmiştir. Çalışmamız eserin muhtelif nüshalarının karşılaştırılmasından hareketle aralarındaki farklılıkları göstererek, yazarın amaçladığı şekilde düzenlenmiş bir metin üretmeyi ve bu metnin tahlilini hedeflemektedir.

The work titled “el-ʿAkāʾidü'l-ʿAdudiyye,” in which Adud al-Din al-Iji (d. 756/ 1355), an important scholar of theology, methodology, and language from the 8th (14th) century, expounds upon the Ash‘ari theological doctrine, has been the subject of commentary and annotations by numerous scholars. One of these commentaries is “el-Fevâʾidu’s-seniyye fî şerhi’l-ʿAkāʾidi’l-ʿAdudiyye”, authored by Suleyman Fâzıl Afandi (d. 1134/ 1722), who was the preacher and hadith scholar of the pulpit at Hagia Sophia. This study focuses on the life and works of Süleyman Fâzıl Efendi, and it provides a critical analysis and edition of “el-Fevâʾidu’s-seniyye fî şerhi’l-ʿAkāʾidi’l-ʿAdudiyye”. Within this context, various copies of the commentary are introduced, their distinguishing features are highlighted, and information is provided regarding the title of the work, its attribution to the author, the method employed by the author in the commentary, and the sources he consulted. This study aims to produce a text arranged in the manner intended by the author by comparing various copies of the work and demonstrating the differences among them, with the ultimate goal of analyzing his text.
Sulayman Fadil Afandi’s al-Fawaid al-saniyya fi sharh al-Aqaid al-Adudiyya : Critical edition and analysis
Keywords: Adud al-Din al-Iji; Adudüddîn el-Îcî; Akaid ve kelam; al-Aqaid al-Adudiyya; al-Fawaid al-Saniyya; Aqaid and kalam; el-Akaidü’l-Adudiye; el-Fevâidü’s-Seniyye Kalam; Islam; İslam; Kelam; Suleyman Fâzıl Afandi; Süleymân Fâzıl Efendi; Süleymân Fâzıl Efendi (ö. 1134/ 1722); Teoloji (Kelam); Theology